UJI TOKSISITAS AKUT DAN TERTUNDA FRAKSI BUTANOL DAUN AKAR KAIK-KAIK (Uncaria cordata (Lour) Merr.) PADA MENCIT PUTIH (Mus musculus L.) - Meiriza Djohari; Tania Tiara Efendi; Noveri Rahmawati; Husnawati Husnawati; Fina Aryani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Uncaria cordata is a plant that is used to treat diabetes and has antioxidant properties. Research has been carried out on Acute and Delayed Toxicity Tests of Butanol Fraction of Leaves of Kaik-Kaik Root Plant (Uncaria cordata (Lour) Merr.) on Male White Mice (Mus musculus L. This study aims to determine the effect of acute toxicity of the butanol fraction of the leaves of kaik-kaik root by determining the LD50 value. Observations made in this test were the number of dead animals, toxic symptoms, and observations of the organs of the test animals. Observations were made for 24 hours to determine the LD50 value to 14 days after administration of the test preparation. In the observation of toxic symptoms, there were no tremors, seizures, salivation, diarrhea, lethargy, weakness, sleep, and coma in each experimental animal. In the relative weight parameters of organs consisting of the heart, liver and kidneys, there was no effect of this fraction, and there was no change when compared to the control group. The results showed LD50 values > 5000 mg/kgBB are considered relatively harmless and potentially as standardized herbal medicine